O psicólogo clínico e a religiosidade do cliente: impactos na relação terapêutica - Luczinski, Giovana Fagundes (2005)
The observation of the clinical practice of phenomenological oriented psychologists allows us to notice a dissonance in the attitude of great part of these professionals, who, although dispose themselves to receive the human being in his totality, considering all kinds of experiences, don t keep this attitude before the religiousness theme. Beginning from this informal observation, the objective of this master s thesis is to comprehend what are the difficulties these psychologists meet when they face religiousness themes in the therapeutic session. In order to reach this purpose, some interviews have been made with some clinical psychologists who work with the phenomenological approach, guaranteed their competence in this field, who recognize the difficulty in dealing with the theme pointed above, and accept to talk about it. The analyses of the interviews, planed and developed according to the phenomenological method has as a theoretical reference those who prior the human encounter at the clinic as the main way for growth and therapeutic possibilities, mainly Buber, and studious of Psychology and Religion s area. The analyses of the interviews allowed us to evidence the great interference of the personal aspects of the psychologists in their clinical work, in this case, mainly those who refers to their own religiousness, showing its impacts in the therapeutic relation, defining the possibilities of an encounter with the client and the comprehension of his life experience at the present moment